Autonomous unimer-vesicle oscillation by totally synthetic diblock copolymers: effect of block length and polymer concentration on spatio-temporal structures. Issue 26 (25th April 2017) - Tamate, Ryota; Ueki, Takeshi; Shibayama, Mitsuhiro; Yoshida, Ryo
Abstract : The design principles of the self-oscillating block copolymer architecture to control the biomimetic unimer-vesicle oscillation were studied in detail. Abstract : In this study, factors controlling autonomous vesicle oscillations exhibited by self-oscillating diblock copolymers were investigated. The self-oscillating diblock copolymer contains poly(ethylene oxide) (PEO) as the hydrophilic block and a random copolymer composed of N -isopropylacrylamide (NIPAAm) with side chains of ruthenium tris(2, 2′-bipyridine) (Ru(bpy)3 ), which catalyzes the Belousov–Zhabotinsky (BZ) reaction, as the self-oscillating block. Recently, our group has reported that a diblock copolymer exhibits a unique autonomous disintegration and reconstruction of the vesicles driven by the periodic redox changes of Ru(bpy)3 in a catalyst-free BZ reaction solution. Nevertheless, the effect of the diblock copolymer architecture on the structure of the vesicles under equilibrium conditions, as well as their oscillation properties under non-equilibrium conditions, has not been clarified thus far. Hence, self-oscillating diblock copolymers with different block lengths were systematically synthesized, and the effects of the block length and polymer concentration on the spatio-temporal vesicle structures were comprehensively discussed.